Optimization of multilayer micro channels heat sinks cooling system using genetic algorithm - Zaidan, Husain (2015)
Cooling of electronic devices is problematic by its nature simply because of the space restriction. Recent advances in high powered miniaturized electronic systems have come at the expanse of very high heat fluxes that pose challenges to thermal management research. Uncontrolled excessive heat may cause thermal fatigue and stresses and the current micro electro-mechanical cooling systems (MEMS) which utilize the single layer micro channel heat sink, introduced a decade ago, may no longer be an adequate solution. Possible extension of the layer of parallel micro channels into a stacked system, by developing two, three, and multi-layer channel systems are being investigated. The design of all these systems depends on several parameters; coolant type, channel geometry, channel dimensions, and the number of the channels. This paper reports a new model for optimizing the thermal resistance, developed based on specific parameters of the dimensions of the channel, the wall width between the channels, and using water as a coolant at 27°C. The outcomes of the model were compared with other published studies. The results showed that the model is valid and reliable for further studies.